Two years of solar wind and pickup ion measurements at comet 67P/Churyumov–Gerasimenko - Goldstein,R; Burch,JL; Mokashi,P; Mandt,K; Carr,C; Eriksson,A; Glassmeier,K-H; Henri,P; Nilsson,H; Rubin,M; Tzou,C-Y (Monthly Notices of the Royal Astronomical Society, 2017)
The Ion and Electron Sensor (IES) as well as other members of the Rosetta Plasma Consortium (RPC) on board the Rosetta spacecraft (S/C) measured the characteristics of the solar wind almost continuously since its arrival at 67P/Churyumov–Gerasimenko (CG) in 2014 August. An important process at a comet is the so-called pickup process in which a newly ionized atom or molecule begins gyrating about the interplanetary magnetic field, is accelerated in the process and is carried along with the solar wind. Within a month after comet arrival, while Rosetta was <100 km from CG, we began to observe low-energy (<20 eV) positive ions. We believe that these are newly formed from cometary neutrals near Rosetta and attracted to the negative S/C potential. These ions were in the early phase of pickup and had not yet reached the energy they would after at least one full gyration about the magnetic field. As CG increased its activity, the flux and energy of the measured pickup ions increased intermittently while the solar wind appeared intermittently as well. By about 2015 end of April, the solar wind had become very faint until it eventually disappeared from the IES field of view. We then began to see ions at the highest energy levels of IES, >10 keV for a few days and then intermittently through the remainder of the mission, but lower energy (a few keV) pickup ions were also observed. As of 2016 early February, the solar wind reappeared more consistently. We believe that the disappearance of the solar wind in the IES field of view is the result of interaction with the pickup ions and the eventual formation of a cavity that excluded the solar wind.